MexAB-OprM Efflux Pump of Pseudomonas aeruginosa Offers Resistance to Carvacrol: A Herbal Antimicrobial Agent - Pesingi, Prasanna Vadhana; Singh, Bhoj Raj; Pesingi, Pavan Kumar; Bhardwaj, Monika; Singh, Shiv Varan; Kumawat, Manoj; Sinha, Dharmendra Kumar; Gandham, Ravi Kumar (Frontiers in Microbiology, 2019)
Carvacrol has been proven to be a potent herbal antimicrobial agent against many pathogens. However, some multi drug resistant strains of Pseudomonas aeruginosa are tolerant to many herbal compounds including carvacrol. The tolerance of Pseudomonas aeruginosa to carvacrol is not well studied. This study aims to identify the gene(s) associated with carvacrol tolerance thus to understand its mechanisms in P. aeruginosa. Herbal drug resistant MDR strain of P. aeruginosa was isolated from the field samples. Carvacrol sensitive mutant was generated using transposon mutagenesis. The inactivated gene in the mutant was identified as mexA, which is a part of mexA-mexB-oprM efflux pump. Inactivation of mexA gene resulted in 32.5 fold reduction in MIC of carvacrol whereas 80 folds reduction was observed in the presence of PAβN. The organism was completely killed within 3 h of incubation in all combinations of carvacrol and PAβN. Interestingly, mexA inactivation did not affect the tolerance of other herbal compounds used. This study reveals that the tolerance of carvacrol in P. aeruginosa is mediated by the MexA-MexB-OprM efflux pump but not to other herbal antimicrobial compounds used in this study